European idiopathic pulmonary fibrosis Patient Charter: a missed opportunity. Issue 1 (July 2016) - Bush, Andrew; Barbato, Angelo; Clement, Annick; Cunningham, Steve; Blic, Jacques de; Gilbert, Carlee; Goldbeck, Lutz; Kiper, Nural; Schwerk, Nicolaus; Griese, Matthias
The European charter for idiopathic pulmonary fibrosis is a welcome document [1], highlighting unmet needs in patients which will inform policy makers across Europe. However, it is sad that an important opportunity to involve children with interstitial lung diseases (ILDs) has been missed. There is a current pan-European paediatric ILD consortium [2] which could have been used to access these children and families. Our own work also highlighted similar themes [3]: diagnostic delay, the need for improved holistic care and written information, and also interestingly highlighted a previously undescribed issue, the high prevalence of feeding disorders in these children. So the European Charter, excellent as it is, sadly represents a lost opportunity to represent the needs of children with rare lung diseases to health commissioners. Children with ILD should also have been included in the IPF European Charter http://ow.ly/ZBfA0